The Asymmetry of Population Ethics: Experimental Social Choice and Dual-Process Moral Reasoning - Dean Spears (Institute of Labor Economics (IZA), 2019)
Population ethics is widely considered to be exceptionally important and exceptionally difficult. One key source of difficulty is the conflict between certain moral intuitions and analytical results identifying requirements for rational (in the sense of complete and transitive) social choice over possible populations. One prominent such intuition is the Asymmetry, which jointly proposes that the fact that a possible child's quality of life would be bad is a normative reason not to create the child, but the fact that a child's quality of life would be good is not a reason to create the child. This paper reports a set of questionnaire experiments about the Asymmetry in the spirit of economists' empirical social choice. Few survey respondents show support for the Asymmetry; instead respondents report that expectations of a good quality of life are relevant. Each experiment shows evidence (among at least some participants) of dual-process moral reasoning, in which cognitive reflection is statistically associated with reporting expected good quality of life to be normatively relevant. The paper discusses possible implications of these results for the economics of population-sensitive social welfare and for the conflict between moral mathematics and population intuition.
Keywords: J10; J13; J18; D63; 330; population ethics; experimental social choice; the Asymmetry; dual-process moral reasoning; questionnaire-experimental method